2019
DOI: 10.1002/jor.24323
|View full text |Cite
|
Sign up to set email alerts
|

Safe Supra‐Acetabular Pin Insertion in Relation to Intraosseous Depth

Abstract: In pelvic fractures, dysfunction of the pelvic ring is often stabilized with supra-acetabular pin insertion. In existing literature, there are heterogeneous indications on proper pins selection and inclinations. Therefore, this study aimed to quantify the narrowing of safe pin corridors in the transverse and sagittal planes with increments of intraosseous screw depths. A computer algorithm created cross-sections over three-dimensional pelvic reconstructions at sagittal inclinations from 45°cranial to 45°caudal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…While the focus of this study is on the mechanical properties of the external fixator, imaging-related factors require equal attention to maximise stability while www.nature.com/scientificreports/ maintaining a clinically acceptable level of MRI quality 21,22 . Additional limitation of the study is given by the fact that single lengths for the screws were used while studies performed by Morandi et al 23 and Young et al 24 have proven that for these insertion points multiple trajectories and pin lengths are safe to be used.…”
Section: Discussionmentioning
confidence: 98%
“…While the focus of this study is on the mechanical properties of the external fixator, imaging-related factors require equal attention to maximise stability while www.nature.com/scientificreports/ maintaining a clinically acceptable level of MRI quality 21,22 . Additional limitation of the study is given by the fact that single lengths for the screws were used while studies performed by Morandi et al 23 and Young et al 24 have proven that for these insertion points multiple trajectories and pin lengths are safe to be used.…”
Section: Discussionmentioning
confidence: 98%
“…Present results are comparable with those by other authors. The Morandi [ 12 ] explored the narrowing ranges of safe insertion with increasing screw lengths in the supraacetabular area and the relationship between anatomical size of the pelvis and screw size. The author concluded that the 60 mm screw depth provided the best option to limit breaching of the pelvic wall having the largest range in both transverse and sagittal directions.…”
Section: Discussionmentioning
confidence: 99%
“…Young et al [ 20 ] sectioned the pelvis by reconstructing three-dimensional model of the pelvis to determine the greatest degree of sagittal pin spanning angulation between two iliac crest pins and how intraosseous depth affects these angulations. Morandi et al [ 12 ] also designed the study that A computer algorithm created cross‐sections over three‐dimensional pelvic reconstructions to quantify the narrowing of safe supra‐acetabular pin corridors in the transverse and sagittal planes with increments of intraosseous screw depths. All the measures we performed were based on different entry points.…”
Section: Discussionmentioning
confidence: 99%
“…10,13 The use of shading scanners, fluoroscopybased imaging, three-dimensional C-arm, preoperative CT-based planning, computer navigation, and robot-assisted techniques have also shown promising results in ensuring accurate and safe screw placement while minimizing the risk of SGA injury. [15][16][17][18]…”
Section: Prevention Of Sga Injurymentioning
confidence: 99%